PREVENTION OF INFECTIOUS DISEASES OF A WIDE ORDER AMONG THE POPULATION AND ROLE OF A HEALTHY LIFESTYLE - Xasanova Shoiraxon Abdujabborovna; Kodirov Sherzodbek Xusanboy o’gli (Journals Park Publishing, 2023)
Profilaftics, pathogenic microorganism, preventive and epidemic, COVID-19, buster dose, geographical environment, diarrhea, infections
Keywords: AKDS, national calendar,tetanus, polio, measles